VARIASI BAHASA DAN JENIS BAHASA MAHASISWA PERANTAU PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA ANGKATAN 2022 DI UNIVERSITAS PGRI KALIMANTAN - Norhasanah, Laila; Wulandari, Noor Indah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is based on the phenomenon of linguistic diversity among migrant students, which influences language use in daily interactions within the campus environment. The purpose of this study is to analyze the language variations and language types used by migrant students of the Indonesian Language and Literature Education Study Program, class of 2022, at Universitas PGRI Kalimantan. This study employs a descriptive qualitative approach, with data collected through observation, recording, note-taking, and documentation of students’ utterances. The data were analyzed based on sociolinguistic theories of language variation and language types. The results show that the language variations found include variations based on speakers (dialect and idiolect), usage (register), formality (formal, casual, and consultative styles), and medium (spoken and written language). The most dominant variation is the Banjar dialect, which is widely used in informal communication among students. Meanwhile, the types of language identified include sociological aspects, language attitude, language acquisition, and the function of language as a lingua franca. Banjar language functions as a regional lingua franca in social interactions, while Indonesian is used in formal academic contexts. This study concludes that migrant students demonstrate strong linguistic adaptability by utilizing various language variations and types according to communicative contexts and needs. It also highlights the role of regional languages as both identity markers and effective tools for social communication within the campus environment.